Enhancing Ambiguity Tolerance in Counsellors-in-Training: A Pilot Program - Spinelli, Christina; Ibrahim, Marim; Khoury, Bassam (Canadian Journal of Counselling and Psychotherapy, 2025)
The inherent ambiguity of therapy is a significant source of stress for novice counsellors-in-training. As such, the development of their ability to tolerate ambiguity is an important task within their clinical development. The authors sought to examine the effects of a novel 6-week mindfulness and compassion program on ambiguity tolerance and well-being measures in counsellors-in-training working with clients for the first time. Twenty-three counsellors-in-training from across Canada completed measures of ambiguity tolerance, mindfulness, self-compassion, psychological distress, and life and work satisfaction at baseline, post-training, and 3-month follow-up. Participants also provided brief written feedback on the program to assess its feasibility and acceptability. Non-parametric analyses revealed significant increases in the epistemic dimension of ambiguity tolerance, overall meditative mindfulness, self-warmth, and life satisfaction at post-training and follow-up. All participants recommended this training to other students and reported increased knowledge of mindfulness, compassion, and ambiguity tolerance. Future studies should assess this program using a controlled design.